THE EFFECTIVENESS OF USING FIX UP STRATEGY TOWARD THE STUDENTS’ READING COMPREHENSION - Jamila Said; Abdul Muis Said; Muh Rusydi Rasyid (Universitas islam Negeri Alauddin Makassar, 2020)
The aim of this research is to determine the effectiveness of using fix-up strategy on the students’ reading comprehension at MA AL-Wasilah Lemo. The population in this research was the second grade students of MA Al-Wasilah Lemo. The sample was consisted of 30 students which were taken by total sampling technique. There were 15 students in class Agama II 1 as experimental class and 15 students in Agama I as controlled class. This research was quasi experimental with the Nonequivalent Control Group Design. The data was analyzed statistically after the result of the test was gained.The research findings showed that the twelve grades students of MA Al-Wasilah Lemo obtained score on pre-test with the mean score 44.00 which classified as poor. After giving treatment the students obtained improvement, they gained score with the mean score 65.00 as fair classification. The result of the data analysis indicated that there was a significant improvement in the students reading analytical exposition text after being taught using fix-up strategy. It was proved by the result of the statistical analysis of the level significance 0.05 with degree of freedom (df) 14 indicated t-test values of the students’ reading analytical exposition text (5.209) was higher than t-table value (2.145). Based on the result of analysis, the researcher concludes that fix-up strategy was effective to improve students in reading comprehension at the twelve grade of MA Al-wasilah Lemo.